Pengolahan Antibiotik Tetrasiklin Menggunakan Komposit TiO2-Zeolit yang Disintesis Menggunakan Metode Hidrotermal dengan Memvariasikan Massa TiO2:Zeolit - Najwa Ziinatul Aimmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Tetracycline is an antibiotic that is widely used in aquaculture systems. Disposal of waste that still contains tetracycline without treatment can pollute the environment. The treatment that can be done is using the photocatalysis method with a TiO2-ZA composite to degrade the tetracycline solution. The composite was synthesized by the hydrothermal method for 12 hours at a temperature of 220oC. The composite material was varied in the mass ratio of TiO2-ZA 5%, TiO2-ZA 10%, TiO2-ZA 15%, TiO2-ZA 20%, TiO2-ZA 25%, dosage 0.1 g, 0.3 g, and 0.5 g, and solution pH 5, pH 7, and pH 9. Photocatalytic tests were carried out under UV-Vis light for 6 hours. The results showed that the 20% TiO2-ZA composite with a dosage of 0.3 g at pH 7 had the highest photocatalytic activity. SEM-EDX and BET characterization showed good particle distribution at a ratio of 20%. If a material has excess TiO2, it can reduce the pore area. Thus, the TiO2-ZA composite was proven to be effective as a photocatalyst for the treatment of tetracycline waste.
Reupload file repository 16 Maret 2026_Ratna
Keywords: TiO2-ZA; tetracycline; mass ratio; dosage; solution pH